Penile Vibratory Stimulation for Semen Retrieval in Men with Spinal Cord Injury: Patient Perspectives - Ibrahim E; Brackett NL; Lynne CM (Research and Reports in Urology, 2022)
Emad Ibrahim,1,2 Nancy L Brackett,1,2 Charles M Lynne1,2 1The Desai Sethi Urology Institute, University of Miami Miller School of Medicine, Miami, FL, USA; 2The Miami Project to Cure Paralysis, University of Miami Miller School of Medicine, Miami, FL, USACorrespondence: Emad Ibrahim, The Desai Sethi Urology Institute/The Miami Project to Cure Paralysis, University of Miami Miller School of Medicine, 1611 NW 12th Ave, 2nd floor, Rm 2.147, Miami, FL 33136, USA, Tel +1 305 243 9083, Fax +1 305 243 3913, Email eibrahim@miami.eduAbstract: Spinal cord injury (SCI) is a catastrophic event with sequelae that are not often apparent. For the spinal cord injured man, the inability to become a biologic father because of reproductive dysfunction becomes a major negative factor in his self-esteem and a hindrance to his social rehabilitation. Approximately, 90% of men with SCI develop ejaculatory dysfunction and only 10% can ejaculate by masturbation or during sexual activity. It is only over the last 40 years that it has been possible to properly study and understand the various factors contributing to the problem. Advances have been made in governmental and societal attitudes that have led to improvements in the treatment and rehabilitation of persons with SCI and other disabilities. It is now possible to retrieve sperm reliably and safely from men with SCI. Although their semen quality is often impaired, there is a very reasonable chance for achieving biologic fatherhood using assisted reproductive techniques. Penile vibratory stimulation (PVS) is a safe, reliable, efficient, and cost-effective, method of sperm retrieval that will produce an ejaculate in up to 86% of the patients with a level of injury T10 or rostral, which accounts for approximately 80% of the SCI population. Some motile sperm will be present in 90% of these ejaculates. In approximately 75% of the ejaculates, there will be greater than 5 million motile sperm, allowing a couple to explore all the options available to a couple seeking help in conceiving a child. The Male Fertility Program of the Miami Project to Cure Paralysis is at the leading edge of basic and clinical research contributing to the management of infertility in men with SCI. This review will outline “how we got there” enabling us to recommend PVS as the first choice in assisting men with SCI to become biologic parents.Keywords: anejaculation, fertility, sperm, conception, reproduction, child